Effects of Non-Conventional Substrate and NPK Fertilizer on Cassava Plantlets Acclimatization for Plant Material Production - CACAÏ, Gilles Habib Todjro (My University, 2021)
The adaptation of cassava plantlets to natural conditions remains the main obstacle in the process of free virus plantlets production. In this study, cassava plantlets acclimatization was assessed by pre-acclimatization, height of acclimated plantlets, substrate, and nutrient watering solution. The results revealed that pre-acclimatization gave a high survival rate (61.9%) whereas the direct tunnel acclimatization was conducted to low rate (27.31%) of plantlets. Furthermore, the height of plantlets influenced significantly (p < 0.05) their survival rate with best survival rate observed on plantlet height from 1 cm to 5 cm. There was no significant difference between the substrates used and watering solutions. However, the Sawdust substrate gave a high survival rate (46.67%) and better phylogenesis (1.8) in the variety RB 89509. Likewise, plantlets treated with NPK nutrient watering solutions (20-10-10) had a better survival rate (48.57%), better phylogenesis (2.125) with the variety RB 89509 and better growth in height (1.18 cm) with the variety BF92/0267. These findings constitute a database for the establishment of the technical itinerary for the acclimatization of cassava plantlets
Keywords: Manihot esculenta; Plantlets; Pre-Acclimatization; Substrates; Nutrient; Solution; NPK